The Improving Legal Students’ Vocabulary by Using Duolingo at First Semester in Universitas Muhammadiyah Papua - Irfun, Irfun (Lembaga Riset Ilmiah, 2024)
Vocabulary mastery plays a pivotal role in legal education, where precise language understanding determines the accuracy of reasoning, interpretation, and communication within academic and professional contexts. This study investigates the effectiveness of Duolingo, a gamified digital language learning platform, in improving the vocabulary mastery of first-semester law students at Universitas Muhammadiyah Papua. Grounded in Krashen’s Input Hypothesis, Schmidt’s Noticing Hypothesis, and Constructivist learning theory, the research adopts a quantitative experimental design employing pre-test and post-test procedures. Twenty students participated in the study, with vocabulary tests administered before and after a Duolingo-based learning intervention. Statistical analysis using IBM SPSS revealed a significant improvement in students’ mean scores—from 70.33 (pre-test) to 80.83 (post-test)—with a p-value of .000 (<0.05), confirming a substantial positive effect of the intervention. The findings demonstrate that Duolingo’s adaptive feedback, gamification elements, and contextualized vocabulary activities effectively enhance learners’ retention and engagement. These results underscore the potential of integrating mobile-assisted language learning tools into legal education to address the challenges of low motivation and limited exposure to specialized terminology. The study concludes that Duolingo offers a practical, engaging, and empirically supported alternative for developing legal vocabulary competence among novice law students in higher education contexts.